EVALUTION OF CONTAMINATION STATUSE IN IMPORTED AND LOCAL TABLE EGGS - M. F. Hamood,; H.N.Jasim,; A.S.A.AL-Hassani, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was conducted to detect the contamination in the local and imported table eggs, and the comparison between them of contamination.  Samples were collected from local markets   taking 60 samples of both types (30 local eggs and 30 imported eggs) these samples were sent to a laboratory of microbiology / College of Veterinary Medicine / University of Baghdad .then taking swabs from the   different of eggs shells samples for both types (local and imported eggs) then bot swabs in nutrient broth to be grown bacteria in the nutrient broth). (After that samples were taken from the nutrient broth) and then cultured in the (nutrient agar, macconky agar). The results showed the presence of bacterial growth (E. Coli gram negative on the macconky agar) in the samples that have been taken from local eggs. While the results showed the samples that were taken from imported eggs indicate the presence of bacterial growth ((bacteria gram positive. Staphylococcus spp.), (Streptococcus spp.))  as well as bacteria bacilli gram negative growth on the nutrient agar. While the results of bacterial count showed the presence of bacterial growth more in imported eggs compared to local eggs ,Imported eggs(B) (8.6 × 106 log cfu / ml). Compared to the totals local egg (A) where the results (2.1 × 104 log cfu / ml). (Table no.1) .The results appear of high contamination in imported eggs compared with local eggs.